2010
DOI: 10.1073/pnas.1009443107
|View full text |Cite
|
Sign up to set email alerts
|

Glatiramer acetate triggers PI3Kδ/Akt and MEK/ERK pathways to induce IL-1 receptor antagonist in human monocytes

Abstract: Glatiramer acetate (GA), an immunomodulator used in multiple sclerosis (MS) therapy, induces the production of secreted IL-1 receptor antagonist (sIL-1Ra), a natural inhibitor of IL-1β, in human monocytes, and in turn enhances sIL-1Ra circulating levels in MS patients. GA is a mixture of peptides with random Glu, Lys, Ala, and Tyr sequences of high polarity and hydrophilic nature that is unlikely to cross the blood–brain barrier. In contrast, sIL-1Ra crosses the blood–brain barrier and, in turn, may mediate GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…An earlier study showed the ability of GA to induce sIL-1Ra expression via the activation of PI3K, AKt, MEK1/2, and ERK1/2 [55]. However, PD-98059 (10 mM) was not found to Cellular Physiology and Biochemistry…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…An earlier study showed the ability of GA to induce sIL-1Ra expression via the activation of PI3K, AKt, MEK1/2, and ERK1/2 [55]. However, PD-98059 (10 mM) was not found to Cellular Physiology and Biochemistry…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…There is also evidence to suggest that GA, in addition to its action on the adaptive immune system, acts on the innate immune system by directly modulating the activity of myeloid cells, in particular monocytes and dendritic cells [39][40][41][42]. The properties of monocytes of RRMS patients undergoing treatment with GA have been compared with those of untreated patients and of healthy controls, showing that monocyte reactivity was inhibited in the treated patients.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…43 IL-1b, in turn, induces specifically the expressions of IL-1b and sIL-1Ra, as shown in cultured human endometrial stromal cells. 44 In diabetic tissues, such as the cornea, impairment of PI3K and ATK signaling, because of impaired epidermal growth factor receptor signaling, 25 may differentially affect sIL-1Ra production, as shown in human monocytes, 45 resulting in an imbalance of IL-1b and sIL-1Ra, leading to delayed epithelial wound healing (Figure 9).…”
Section: Il-1ra and Diabetic Cornea Wound Healingmentioning
confidence: 99%